Soil-foundation-structure Interaction : selected papers from the International Workshop on Soil-Structure Interaction (SFSI 09), Auckland, New Zealand, 26-27 November 2009 /: selected papers from the International Workshop on Soil-Structure Interaction (SFSI 09), Auckland, New Zealand, 26-27 November 2009. (©2010) - Unknown
No abstract available